What can a tandem of a pathophysiologist and a clinician bring to clinical practice? - A.I. Gozhenko; D.D. Ivanov (Počki)
Kidney diseases, starting from acute kidney injury, acute kidney disease, or having an uncertain onset, often progress to chronic kidney disease (CKD). The pathomorphosis of this progression typically involves predominant damage to the glomerulus, affecting either the glomerular filter or the tubules, primarily in the proximal part. International guidelines identify two key indicators for determining the prognosis and progression of CKD: albuminuria and glomerular filtration rate. Additional criteria, such as blood pressure, pathomorphological changes, or multifactorial calculators, are usually proposed for specific nosological forms. However, accurately predicting CKD progression remains a challenging issue. We propose using renal functional reserve to estimate the number of functioning nephrons. Together with blood pressure, degrees of albuminuria, and glomerular filtration rate, this approach provides a more accurate assessment of the future course of CKD.